SELEKSI CALON POHON PLUS KILEMO (Litsea cubeba) DI GUNUNG LEMO KABUPATEN CIANJUR JAWA BARAT - Ina Darliana; Elis Nurmawanti (Wanamukti: Jurnal Penelitian Kehutanan, 2021)
Kilemo (Litsea cubeba) is a forest plant that has high economic value such as essential oils which can be used as raw materials for various biopharmaceutical industries such as soap, perfume, medicines, and aromatherapy. This potential has not been developed by the surrounding community as a commodity for industrial raw materials due to public ignorance in cultivating, besides the difficulty of getting seeda from kilemo itself is another reason for residents to cultivate these plants. The object of research is to identify prospective of trees plus of kilemo. The selction of plus trees was carried out using a purposive sampling system by placing units using random start method and selecting the tree heigt and diameter according to the plus tree scoring table. There were 29 prospective trees plus of kilemo identified according to their phenotypic appearance with the following characteristics: the average total tree heigt was more than 10 m (20-36 m), the branch-free height was realtively low, and the largest diameter was 32 cm. In addition, it was also found to be fruiting and flowering at 72,41%, only 17,24% to bear fruit and 10,34% to flower.